Switching to nebulised short acting bronchodilators does not increase the risk of arrhythmia in patients hospitalized with a COPD exacerbation. (November 2021) - Santus, Pierachille; Franceschi, Elisa; Pini, Stefano; Frassanito, Francesca; Amati, Francesco; Danzo, Fiammetta; Gatti, Marina; Radovanovic, Dejan
Abstract: If short acting β2-agonists and muscarinic antagonists (SABA/SAMA) may have proarrhythmic effects during acute COPD exacerbations (AECOPD) is still unknown. The primary objective of the study was to investigate the incidence of new onset arrhythmias in hospitalized patients shifted to SABA/SAMA during an AECOPD compared with continuing chronic inhaled therapy. Secondary objectives were to assess the clinical characteristics of patients shifted to SABA/SAMA and risk factors for arrhythmia. This was a retrospective, observational, study enrolling consecutive patients hospitalized with an AECOPD. Incidence of arrhythmias was obtained reviewing digital records. Patients with chronic arrhythmias or home-treated with SABA/SAMA were excluded. 235 patients (63.8% males) were included, and 10/182 patients shifted to SABA/SAMA experienced arrhythmias, while no events were observed in patients on chronic inhaled therapy (p = 0.122). Shifted patients had a more severe AECOPD and history of paroxysmal atrial fibrillation was an independent risk factor for arrhythmia (OR 14.010, IC95%: 2.983–65.800; p = 0.001). In conclusion, shifting patients to SABA/SAMA appears not to increase the risk for arrhythmia during severe AECOPD. However, the pharmacological approach in patients with a history of paroxysmal arrhythmia should be carefully evaluated and monitored. Graphical Abstract: ga1 Highlights: The pro-arrhythmic effect of short acting bronchodilators in COPD patients is questioned. We tested if hospitalized patients shifted to SABA/SAMA had higher risk of arrhythmia. Of 235 COPD patients with acute exacerbation, 77.5% were shifted to SABA/SAMA. New onset arrhythmias were observed only in patients shifted to SABA/SAMA. The only risk factor for arrhythmia, however, was paroxysmal atrial fibrillation.